Cloud Computing in Education and Its Advantages - Usmonov, Muhammadabdulla (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article provides a comprehensive overview of the concept of cloud computing in modern education, highlighting its significance, advantages, and practical applications. The primary focus is on exploring how cloud computing can be effectively utilized in educational institutions, examining its various forms and real-world examples. Cloud computing facilitates flexible and seamless access to educational resources from any location at any time, thereby transforming the teaching and learning process into a more interactive and efficient experience. The article thoroughly analyzes the key benefits of cloud computing, such as cost reduction, flexible resource access, data security, reliability, scalability, and simplification of educational processes. Furthermore, it addresses the potential drawbacks and risks associated with cloud computing, including concerns related to security, privacy, and the lack of administrative control. International experiences and case studies are also incorporated to illustrate the practical impact of cloud computing in education. In conclusion, the article emphasizes how cloud computing is reshaping the educational landscape and outlines effective strategies for its successful implementation in academic environments.